Children With Intracranial Arachnoid Cysts: Classification and Treatment. Issue 44 (November 2015) - Tan, Zhen; Li, Yongxin; Zhu, Fengjun; Zang, Dongdong; Zhao, Cailei; Li, Cong; Tong, Dan; Zhang, Heye; Chen, Qian
Abstract : Abstract: We performed a dynamic study of arachnoid cysts (ACs) using magnetic resonance cisternography (MRC) and proposed a classification of ACs. Twenty-three suitable patients in our hospital entered into this study according to our inclusion criteria. MRC images were collected in all the subjects at 1 and 24 hours after the administration of intrathecal gadolinium-diethylenetriamine penta-acetic acid (Gd-DTPA). We allocate the enrolled patients into 2 groups, MRC group and surgery group. The MRC results were considered before treatment in 1 group (MRC group, 13 patients), whereas another group was surgically treated without considering the MRC results (surgery group, 10 patients). We calculated the enhanced area of cyst using modified MacDonald Criteria from the images and measured the surrounding subarachnoid area as the reference. We found that it was practically useful to quantify 3 types of ACs, complete communicating, incomplete communicating, and noncommunicating, according to MRC results in this study. All the subjects in both groups are closely observed before the treatment and the follow-up using the MRI examination. In the surgery group, 5 patients were found that the area of cysts shrank in the follow-up stage. However, there was no significant difference in the percentage shrinkage area between the 2 groups. We concluded that MRC with Gd-DTPA as a contrast agent is of significant clinical value for the diagnosis and treatment of children with intracranial ACs. This classification based on dynamic MRC is useful for making surgical recommendations.